UJI AKTIVITAS EKSTRAK ETANOL DAUN BIDARA LAUT (Strychnos ligustrina Biume) TERHADAP PENYEMBUHAN LUKA BAKAR PADA KELINCI (Oryctolagus cuniculus) - Rahimah, Sitti; Salampe, Mirnawati; Syamid, Ahmad Gufairil; Ismail, Ismail; Nisa, Michrun (MEDFARM: Jurnal Farmasi dan Kesehatan, 2023)
Burns are damage or loss of skin tissue caused by contact with heat sources such as hot water, fire, chemicals, electricity, friction and radiation. Sea lotus (Strychnos ligustrina Blume) is known to contain compounds that have the potential to heal burns such as flavonoids, saponins and tannins. This study aims to determine the activity of ethanol extract of bidara de mer leaves on burn healing as a function of reduction in burn diameter, wound discoloration, edema and crust formation. This study used 5 Oryctolagus cuniculus that received 4 types of treatment after being induced by hot plate, namely wound I (bioplacenton® gel positive control), wound 2 (HPMC 5% negative control), wound 3 (extract concentration 10%) and wound 4 (concentration of extract 10%) 25%). Apply the test sample to the burns twice a day and observe the condition of the wound daily. Burn healing as a function of wound diameter was determined based on the AUC (Area Under Curve) value and statistically analyzed using SPSS 21.0. The test results showed that the mean AUC value at 10% and 25% concentrations was 0.495 cm/day and 0.532 cm/day, respectively. The results of the statistical analysis showed that the ethanol extract of bidara sea leaves gave significant results compared to the negative control. treatment (HPMC). The conclusion obtained is that the ethanolic extract of sea bidara leaves accelerates the healing process of burns in Oryctolagus cuniculus.